Global Launch Event For the CGIAR Initiative on National Policies And Strategies For Food, Land And Water Systems Transformation (NPS) - Kassim, Yumna (International Food Policy Research Institute, 2022)
On Tuesday, May 17th, 2022, on the ILRI Campus in Nairobi, Kenya, the National Policies and Strategies for Food, Land and Water Systems Transformation (NPS) Initiative held its launch event. NPS is a new One CGIAR initiative that has been co-created with national and international partners with the main objectives of building policy coherence, responding to crises, and integrating policy tools at national and subnational levels in six countries in Africa, Asia and Latin America. The initiative is expected to make substantial, research-based contributions to improve food and water security, nutrition and livelihoods; reduce poverty and support job creation, gender equality and social inclusion; and find solutions for climate change adaptation.